2010
DOI: 10.1158/1940-6207.capr-09-0272
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Colitis-Associated Carcinogenesis with Infliximab

Abstract: The emergence of infliximab was an epochal event in the treatment of inflammatory bowel disease (IBD). Because colitis-associated cancers arose in the setting of chronic inflammation, during which "inflammation-dysplasia-carcinoma sequence" prevails and anti-inflammatory agents can prevent carcinogenesis, we hypothesized whether infliximab can prevent colitic cancer in animal models for which C57BL/6 mice were exposed to 15 cycles of dextran sulfate sodium (DSS), with each cycle consisting of 0.7% DSS for 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 43 publications
5
65
0
1
Order By: Relevance
“…Although there are no data available whether IBD patients non-responding to IFX therapy are at an increased risk for colon cancer, an animal study indicated that IBD animals treated with IFX are protected from colon cancer [22][23][24][25][26][27][28][29]. Therefore, one may also speculate that patients having high Wnt5a gene expression may be subjected to IFX non-responsiveness and, also, are at a higher risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no data available whether IBD patients non-responding to IFX therapy are at an increased risk for colon cancer, an animal study indicated that IBD animals treated with IFX are protected from colon cancer [22][23][24][25][26][27][28][29]. Therefore, one may also speculate that patients having high Wnt5a gene expression may be subjected to IFX non-responsiveness and, also, are at a higher risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse colorectal cancer model, TNFa and one of the major prostaglandins, PGE 2 , induce tumorigenesis via an aberrant activation of NF-kB or Wnt/b-catenin signaling in epithelial cells (3,4). Consistently, clinical studies have shown that treatment with an anti-TNFa antibody or a COX inhibitor is effective against the development of human colorectal cancer (5,6). However, each COX metabolite PG or TNFainduced cytokine possesses a pro-or an anti-inflammatory role and acts coordinately to govern inflammatory responses, eliminate foreign objects, and remodel tissues.…”
Section: Introductionmentioning
confidence: 87%
“…As shown in vivo on a mouse model of CACRC, only 16.7% of animals treated intravenously with infliximab at dose 4 mg kg -1 for 37 weeks developed tumors vs. 75-80% of control mice [57]. This suggests that the early and intensive therapy with infliximab may prevent the development of CACRC in high-risk IBD patients.…”
Section: Anti-tnf-α Agentsmentioning
confidence: 88%